Evaluating a mindfulness intervention for improving sleep and mental health in university students - Oldjohn, Theophilus (Department of Psychology, 2025)
Mental health, including depression and anxiety, difficulties are one of the biggest challenges that university students face. These difficulties have an impact on other aspects of functioning such as sleep quality and quantity. However, studies show a bidirectional relationship between sleep and mental health challenges, hence continous poor sleep may lead to increased symptoms of anxiety and depression. Mindfulness has been recognised as an accessable treatments used to improve sleep and reduce mental health problems. The objective of this study was to evaluate mindfulness as an intervention for poor sleep, and subsequent mental health challenges in university students. The participants were divided into two groups, an intervention group (n = 20) that received mindfulness training and a control group (n = 18) that did not. The treatment intervention consisted of a daily 20- minute audio guided exercise which was completed over a 7-day period. I measured sleep quality, depressive and anxiety-related symptoms, and academic performance before and after the intervention/control period. Results showed no improvement in sleep quality and anxiety- related symptoms between the intervention and control groups. However, there was a decrease in depressive symptoms in participants who completed the mindfulness intervention. These findings highlight the positive influence of mindfulness on depressive symptoms in university students. However, future studies should further investigate the associations between mindfulness, sleep quality and mental health outcomes in students, who are vulnerable to a high burden of mental health difficulties.